Pengaruh Pelatihan dan Pengembangan SDM terhadap Kinerja Karyawan Rumah Sakit Muhammadiyah Palembang - Putri, Rensi Ayumi; Choiriyah, choiriyah; Cahyani, Eni (Training & Research Institute - Jeramba Ilmu Sukses, 2025)
The problem in this research is whether training and human resource development influence the performance of employees at the Palembang Muhammadiyah Hospital. This research aims to determine the influence of training and human resource development on the performance of employees at the Palembang Muhammadiyah Hospital. In this research, the sample taken was 69 employees. The sampling method used was the stratified random sampling method, chosen for its ability to provide a representative sample. This type of research includes associative research, a comprehensive approach to understanding the relationship between variables. The primary and secondary data used in this research are primary and secondary data, ensuring a thorough understanding of the topic. The data collection techniques used were interviews, questionnaires, and observation—a quantitative method with multiple linear regression analysis chosen for its ability to provide precise results. The results of hypothesis testing show a t-value of 7.580 t-table 1.66827, meaning the influence of training and development of human resources on the performance of employees at the Palembang Muhammadiyah Hospital. The calculated F-value 75.111 > F-table 2.74, then Ho is rejected. Ha is accepted, which means the influence of training and development of human resources on the performance of employees at the Muhammadiyah Hospital Palembang, both partially and simultaneously.